Pan-Cancer Molecular Characterization of m6A Regulators and Immunogenomic Perspective on the Tumor Microenvironment - Zhu, Jie; Xiao, Jiani; Wang, Min; Hu, Daixing (Frontiers in Oncology, 2021)
Purpose: N6-methyladenosine (m6A) methylation plays a critical role in diverse biological processes. However, knowledge regarding the constitution of m6A on tumor microenvironment (TME) and tumor-infiltrating lymphocytes (TILs) across cancer types is still lacking. Methods: We comprehensively analyzed the properties of m6A regulators in genomic profiles from The Cancer Genome Atlas (TCGA) according to expression perturbations of crucial IRGs, CD274, CD8A, GZMA, and PRF1. The four IRGs were proved to be reliable biomarkers of TILs and TME via CIBERSORT and ESTIMATE analyses, and their co-expression relationship was certified by TIMER analysis. Expression variants of IRGs and m6A regulators were verified among TME clusters. Meanwhile, the correlation between m6A regulators and tumor mutational burden (TMB) were tested. Finally, the impacts of IRGs and TME clusters in clinical characteristics and outcomes were revealed. Results: CD274, CD8A, GZMA, and PRF1 showed similar TILs characteristics, of which the level of T cells CD8 and T cells CD4 memory activated are consistent with the expression levels of the four IRGs and higher immune infiltration. All of four IRGs showed impact between tumor pathological stages or clinical outcomes. Among TME type I to type IV, m6A regulators' expression drift changed from high-level to low-level in ESCA, BLCA, HNSC, CESC, BRCA, and GBM. However among TME type V to type VIII, m6A regulators drew a shift from low-level to high-level expression in CESC, BLCA, ESCA, KIRP, HNSC, BRCA, KIRC, COAD, LAML, GBM, and KICH. In ssGSEA analyses, IRGs’ expression levels were elevated with the immune infiltration degree and m6A regulators’ expression level varied among three TILs subgroups. With different TMB levels, expression differences of m6A regulators were observed in BLCA, BRCA, COAD, LGG, LUAD, LUSC, STAD, THCA, and UCEC. Conclusion: We identified four crucial IRGs affecting TILs, TME characteristics and clinical parameters. Expression variants of m6A regulators among the subgroups of TME types and ssGSEA clusters suggested that m6A regulators may be essential factors for phenotypic modifications of IRGs and thus affecting TME characteristics across multiple tumor types. Keywords: N6-methyladenosine methylation, tumor microenvironment, tumor-infiltrating lymphocytes, TCGA, pancancer analysis.